2016
DOI: 10.1111/sms.12754
|View full text |Cite
|
Sign up to set email alerts
|

Role of carbohydrate in central fatigue: a systematic review

Abstract: Carbohydrate (CHO) depletion is linked to neuromuscular fatigue during exercise. While its role at peripheral level is relatively well understood, less is known about its impact centrally. The aim of this systematic review was to critically analyze the effects of CHO on central fatigue (CF) assessed by various neurophysiological techniques. Four databases were searched using PRISMA guidelines through February 2016. The inclusion criteria were: CHO as intervention against a placebo control, fatigue induced by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
0
17
0
4
Order By: Relevance
“…In particular, BCAA were shown to positively impact the rating of perceived exertion (RPE) [14] and performance [21,22]. However, due to the great heterogeneity of the experimental protocols and formulations used, the results of these studies are not always unequivocal; hence, the actual efficacy of BCAAused alone or combined with other components -remains a much debated issue [15,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, BCAA were shown to positively impact the rating of perceived exertion (RPE) [14] and performance [21,22]. However, due to the great heterogeneity of the experimental protocols and formulations used, the results of these studies are not always unequivocal; hence, the actual efficacy of BCAAused alone or combined with other components -remains a much debated issue [15,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Actualmente, se sabe que el rendimiento deportivo está regulado por la disponibilidad de sustratos energéticos, ante la falta de CHO el sistema nervioso recibe señales que dan cuenta de una disminución generalizada de su utilización a nivel celular; la célula pasa de consumir Adenosin-trifosfato (ATP) a producir ATP, induciendo el desarrollo fatiga muscular y la inhibición de síntesis proteica (3)(4)(5)(6) . La literatura recomienda un consumo cercano al 50 a 60% de la ingesta calórica total para población normal, no obstante, estas recomendaciones no son muy específicas en deportistas puesto que generalmente no especifican variables como el tipo de actividad y el nivel del deportista (4,(7)(8)(9) .…”
Section: Introductionunclassified
“…While time to exhaustion could indicate fatigue during endurance exercise, CF is typically observed through the drop-in force-generating capacity (i.e., MVC) alongside other neurophysiological measurements, such as VA, where a reduction indicates lowered neural drive which could originate from spinal and/or supraspinal sites. In our recent review, we summarized that most studies that investigated the effect of CHO on CF did not employ standard neurophysiological techniques to distinguish the peripheral and central involvement of CHO in fatigue (23). Nybo (28) showed that hypoglycemia reduces CAR, whereas CHO supplementation during exercise preserves it.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-exercise consumption of CHO-rich meals has been shown to produced mixed results with respect to time to exhaustion, as discussed in a review by Ormsbee (30); furthermore, only two studies listed by the authors compared the effect of high-versus low-CHO meals. More importantly, to date, there is no study, to our knowledge, that has compared the effects of high and low pre-exercise CHO meals on CF using neurophysiological measures (23). It should be noted that it is difficult and of ethical concern to measure serotonin from cerebrospinal fluid during exercise.…”
Section: Introductionmentioning
confidence: 99%